Methodology of the study of institutional design: Philosophical and critical analysis - Kornievsky, Alexey A. (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика, 2025)
Introduction. In one of its roles political philosophy can act as a theoretical and methodological level of political science, and in this sense is necessary for the full development of the latter. The article presents a philosophical and critical analysis of the problems generated by a simplified understanding of the system approach in political research using the example of studying systems of government. Theoretical analysis. Three main problems have been identified. First, the logical ambiguity of the concept of “system of government”. Second, the violation of the principle of historicism. Third, the violation of the rules for constructing classifications. The basis of all three problems is seen in the incorrect application of the system approach in conducting research. Conclusion. The application and development of a system approach in political research requires the parallel development of a system description language itself. The latter is impossible without referring to philosophical reflection and the application of the principle of “double knowledge”.